Jesus' Sermon on the mount : and his confrontation with the world : an exposition of Matthew 5-10 - Carson, D. A. (Donald A.), 1946- (Toronto ; Grand Rapids, MI : Global Christian Publishers, 1999)
Provides an explanation of the teaching of Jesus in his Sermon on the Mount and the events that follow.
Pt. 1. Jesus' Sermon on the Mount --
Pt. 2. Jesus' confrontation with the world.
Previously published in two vols under the titles The Sermon on the Mount, c1978 and When Jesus confronted the world, c1987.
Includes bibliographical references.
Keywords: Bible. -- Interpretation and criticism; Biblija -- Tumačenje i kritzička analiza; Christian life -- Biblical teaching; Kršćanki život -- Biblijsko učenje